Secretory co-factors in next-generation cellular therapies for cancer - Okuma, Atsushi; Ishida, Yoshihito; Kawara, Taketo; Hisada, Shoji; Araki, Shinsuke (Frontiers in Immunology, 2022)
Since chimeric antigen receptor (CAR) T-cell therapies for hematologic malignancies were approved by the U.S. Food and Drug Administration, numerous “next-generation” CAR T cells have been developed to improve their safety, efficacy, and applicability. Although some of these novel therapeutic strategies are promising, it remains difficult to apply these therapies to solid tumors and to control adverse effects, such as cytokine release syndrome and neurotoxicity. CAR T cells are generated using highly scalable genetic engineering techniques. One of the major strategies for producing next-generation CAR T cells involves the integration of useful co-factor(s) into the artificial genetic design of the CAR gene, resulting in next-generation CAR T cells that express both CAR and the co-factor(s). Many soluble co-factors have been reported for CAR T cells and their therapeutic effects and toxicity have been tested by systemic injection; therefore, CAR T cells harnessing secretory co-factors could be close to clinical application. Here, we review the various secretory co-factors that have been reported to improve the therapeutic efficacy of CAR T cells and ameliorate adverse events. In addition, we discuss the different co-factor expression systems that have been used to optimize their beneficial effects. Altogether, we demonstrate that combining CAR T cells with secretory co-factors will lead to next-generation CAR T-cell therapies that can be used against broader types of cancers and might provide advanced tools for more complicated synthetic immunotherapies.